Risk Factors for Symptomatic Pericardial Effusions Posthematopoietic Stem Cell Transplant - Kelly Lyons; Niti Dham; Bryanna Schwartz; Blachy J. Dávila Saldaña (Journal of Transplantation, 2023)
Background. Pericardial effusions are a known complication posthematopoietic stem cell transplant (HSCT), causing significant morbidity. We aimed to evaluate the risk factors associated with the development of high-grade effusions requiring interventions. Procedure. A retrospective chart review of all HSCT patients over a period of 7 years (2013–2019) in a single institution in the Northeastern United States is conducted. All patients who developed an effusion requiring intervention were included. Patient’s clinical characteristics were compared with all others transplanted during the same time period. Echocardiogram findings of the affected patients were compared to a case-control cohort of unaffected patients with similar age and diagnosis. Chi-square and paired t-tests were utilized to ascertain statistical differences between the groups. Results. A total of 15 patients out of 201 (7.5%) transplanted at our institution developed a moderate or large pericardial effusion requiring pericardiocentesis or a pericardial window. Of this cohort, 13 (87%) underwent a myeloablative preparative regimen, 13 (87%) had cyclophosphamide as part of their regimen, 13 (87%) had recent treatment for viral reactivation, 6 (40%) had an underlying hemoglobinopathy diagnosis, and only 4 (27%) had an active diagnosis of GVHD. A myeloablative preparative regimen had a higher rate of effusion requiring intervention, although it was not statistically significant, and concurrent GVHD was not predictive of effusion development. However, exposure to cyclophosphamide, recent treatment for viral reactivation, and a diagnosis of transplant-associated thrombotic microangiopathy (Ta-TMA) were highly associated with effusions. The latter was associated with increased mortality. The duration of pericardial effusion correlated with the pretransplant echocardiogram left ventricle end diastolic diameter z-score and apical 4-chamber left ventricular peak average strain measurement. Conclusions. Potential risk factors for pericardial effusions post-HSCT include a diagnosis of Ta-TMA, active viral infection, exposure to cyclophosphamide, and a higher left ventricle end diastolic diameter z-score. This information may help guide management for these patients, including identifying high-risk subjects, determining the frequency of echocardiograms, and determining specific echocardiogram measures to follow over time.